"Nodule in Nodule" on Thyroid Ultrasonography: Possibility of Follicular Carcinoma Transformed from Benign Thyroid Tumor. Issue 2 (13th April 2017) - Kobayashi, Kaoru; Ota, Hisashi; Hirokawa, Mitsuyoshi; Yabuta, Tomonori; Fukushima, Mitsuhiro; Masuoka, Hiroo; Higashiyama, Takuya; Kihara, Minoru; Ito, Yasuhiro; Miya, Akihiro; Miyauchi, Akira
Abstract : Background: It is generally considered impossible to differentiate follicular carcinomas from follicular adenomas by means of ultrasonography or cytology before surgery. Therefore, follicular carcinoma is histopathologically diagnosed by verifying capsular and/or vascular invasion after surgery. However, ultrasonography may play an important role in diagnosing follicular carcinoma preoperatively in a small number of cases. Case Description: Four cases of follicular carcinoma or follicular neoplasm that transformed from a benign thyroid tumor and demonstrated a "nodule in nodule" appearance on ultrasonography are presented in this report. Characteristic ultrasound features of such patients are: (1) a "nodule in nodule" appearance, (2) a well-defined boundary line between the nodules, and (3) separate distribution of blood signals within each nodule. Conclusion: A small number of patients with follicular carcinomas or follicular neoplasms may present with a "nodule in nodule" appearance on ultrasonography. It was suggested a long time ago that follicular carcinomas may develop from benign thyroid tumors. The fact that follicular carcinomas appear within benign tumors may be evidence of thyroid tumorigenesis.